Application of lattice Boltzmann methods for the multiphase fluid pipe flow on graphical processing unit. (September 2018) - Cheng, Pengxin; Gui, Nan; Yang, Xingtuan; JiyuanTu,; Jiang, Shengyao
In this paper, we employ the lattice Boltzmann method implemented on compute unified device architecture-enabled graphical processing unit to investigate the multiphase fluid pipe flow. The basics of lattice Boltzmann method as well as the Shan–Chen multiphase model and the fundamentals of graphical processing unit with compute unified device architecture are thoroughly introduced. The procedure of implementation of lattice Boltzmann method on graphical processing unit and the comparison of the computing performance between graphical processing unit and CPU are presented. It is demonstrated that the graphical processing unit-based lattice Boltzmann method has remarkable advantages over CPU especially with selected appropriate parameters. The results of validation cases agree well with previous numerical results or analytical solutions. The vertical and horizontal multiphase pipe flow are simulated and discussed.